2002
DOI: 10.1021/cm011219v
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Co-doped LiMn2O4-Based Spinels. Structural, Electrical, and Electrochemical Characterization

Abstract: High-temperature cubic spinels were obtained by thermal treatment at 1100 °C of the corresponding LiCo y Mn 2-y O 4 (0 e y e 1) spinels. The samples were characterized by X-ray powder diffraction, thermogravimetric analysis, electron paramagnetic resonance (EPR) spectroscopy, and electrical and electrochemical measurements. The lattice parameter of the new phases in the 0.3 < y e 1 range is larger compared to the starting ones. The EPR spectra of the new compounds are also different from the starting ones. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(65 citation statements)
references
References 34 publications
6
58
1
Order By: Relevance
“…Table 1. The lattice parameter of the bare compound matches with the value reported by Song et al [39], and are found to be decreased for the doped spinels due to ionic size effect [40]. This also validate the fact that, the doped transition metal ions replace the Mn 3+ ions, which is bigger in ionic size compared to the Mn 4+ ions [31,39,41].…”
Section: Synthesis and Experimentalsupporting
confidence: 88%
“…Table 1. The lattice parameter of the bare compound matches with the value reported by Song et al [39], and are found to be decreased for the doped spinels due to ionic size effect [40]. This also validate the fact that, the doped transition metal ions replace the Mn 3+ ions, which is bigger in ionic size compared to the Mn 4+ ions [31,39,41].…”
Section: Synthesis and Experimentalsupporting
confidence: 88%
“…The paramagnetic resonance detected here could be attributed to the presence of octahedral Mn 4+ ions that carry a half-integer spin (S=3/2) and are then EPR-active. EPR spectra recorded for as prepared sample shows ( Figure 5) the sharp signal centered at gyromagnetic factor, g ≈ 2 with Lorentzian curve with a peak to peak width (∆H pp ) of 348 mT [31]. This is in accordance with the previous studies of Stoyanova et al [32] and Nayaka et al [21].…”
Section: (S=3/2) Because Of Its Odd Number Of D-electrons Cosupporting
confidence: 90%
“…Manganese based oxides are among the most attractive candidates because of their economical and environmental advantages. Scientists have developed many kinds of Mn oxides, which could be sorted by 3 V (such as LiMnO 2 ) [1,2], 4 V (such as LiMn 2 O 4 ) [3,4] and 5 V (such as LiMn 1.5 Ni 0.5 O 4 ) [5,6] cathode materials in the light of discharge potentials.…”
Section: Introductionmentioning
confidence: 99%